Temporoparietal Junction Functional Connectivity in Early Schizophrenia and Major Depressive Disorder. (December 2018) - Penner, Jacob; Osuch, Elizabeth A.; Schaefer, Betsy; Théberge, Jean; Neufeld, Richard W. J.; Menon, Ravi S.; Rajakumar, Nagalingam; Williamson, Peter C.
Background: The temporoparietal junction (TPJ) has been linked to lower-level attentional and higher-level social processing, both of which are affected in schizophrenia (SZ) and major depressive disorder (MDD). We examined resting functional connectivity of bilateral anterior and posterior TPJ in SZ and MDD to evaluate potential anomalies in each disorder and differences between disorders. Methods: Resting-state functional magnetic resonance imaging data were acquired from 24 patients with SZ, 24 patients with MDD, and 24 age-matched healthy controls. We performed seed-based functional connectivity analyses with seed regions in bilateral anterior and posterior TPJ, covarying for gender and smoking. Results: SZ had reduced connectivity versus controls between left anterior TPJ and dorsolateral prefrontal cortex (dlPFC) and posterior cingulate cortex (PCC); between left posterior TPJ and middle cingulate cortex, left dorsal PFC, and right lateral PFC; between right anterior TPJ and bilateral PCC; and between right posterior TPJ and middle cingulate cortex, left posterior insula, and right insula. MDD had reduced connectivity versus controls between left posterior TPJ and right dlPFC and between right posterior TPJ and PCC and dlPFC. SZ had reduced connectivity versus MDD between right posterior TPJ and left fusiform gyrus and right superior-posterior temporal cortex. Conclusion: Functional connectivity to the TPJ was demonstrated to be disrupted in both SZ and MDD. However, TPJ connectivity may differ in these disorders with reduced connectivity in SZ versus MDD between TPJ and posterior brain regions.